The Matter of Death
XV, 270 p. 18 illus.
Keywords: This collection opens up spaces where lives end, bodies are disposed of and memories generated: hospitals, hospices, care homes, coroners' courts, funeral premises, cemeteries, roadsides, the spirit world. Using material culture studies it illuminates the ways human beings make meaningful the challenges of death, dying and bereavement.